Association of self-reported sleep duration and hypertension: Results of a Chinese prospective cohort study. (17th August 2016) - Wu, Xianming; Sun, Yuemin; Niu, Kaijun; Yao, Wei; Bian, Bo; Yu, Xuefang; Zhao, Huanhuan; Huang, Jingjing
ABSTRACT: Objectives : To examine the association of self-reported sleep duration and hypertension using the data from Tianjin China. Methods : Participants aged 40–70 years without hypertension were recruited with a stratified cluster sampling method across six districts of Tianjin, China. Information regarding their sociodemographic and lifestyle-related characteristics was gathered by questionnaires. After 2 years of follow-up, the second physical examination was taken on the same crowd. Results : During the 2-year period, 874 subjects (221 men, 653 women) were successfully contacted. Multivariate logistic regression was used to analyze the relationship between the frequency of incident hypertension after the 2-year follow-up and sleep duration according to age groups. Among the younger age group (40–<55 years), a short sleep duration (≤ear h) was associated with a significantly higher risk of hypertension compared with sleeping for 7–8 h in unadjusted analyses (OR: 3.15 [95% CI: 1.04–9.54]). In a model after adjustment for the impact factors, a significant difference was also found in the frequency of incident hypertension. Conclusions : In our study, a short sleep duration (≤sho h) is a significant risk factor for hypertension in younger subjects, with no association among older subjects.